Digital Entrepreneurship: The Role of Digital Marketing, Human Capital and Entrepreneurship Orientation On The Success of Small and Medium Culinary Business - Asmawiyah, Asmawiyah; Mukhtar, Afiah; Rahmat, Rahmat (School of Business, IPB University (SB-IPB), 2025)
Background: In the digital transformation era, digital technology is one of the main strategies for business actors to succeed, especially in facing increasingly tight competition. By utilizing digital technology, entrepreneurs can reach a broader market, increase efficiency in operations, and optimize interactions with customers through various digital platforms.Purpose: This research investigates the influence of digital marketing, the role of human capital, and entrepreneurial orientation on the success of small and medium culinary businesses in Makassar City.Design/methodology/approach: This research uses a quantitative approach focusing on Culinary SMEs in Makassar City. The sample in this research was determined using a purposive sampling method with a sample size of 160 respondents. The collected data were then analyzed using the SEM-PLS method with the help of SmartPLS 4 software.Findings/Result: This research shows that digital marketing significantly influences business success, both directly and indirectly, through entrepreneurial orientation. At the same time, human capital is not directly significant to business success but has a significant influence when mediated by entrepreneurial orientation.Conclusion: The growth of entrepreneurship using digital technology is increasing rapidly, showing the importance of technology in supporting business success. The use of digital marketing and the role of human resources through entrepreneurial orientation are essential factors that can increase the success of culinary SME businesses in the digital era.Originality/value (State of the art): his research jointly analyzes the relationship between digital marketing and human capital in supporting business success through entrepreneurial orientation Keywords: digital entrepreneurship, digital marketing, human capital, entrepreneurial orientation, business success